MAKNA FILOSOFIS MADU KULAU DALAM PROSESI UPACARA PERKAWINAN ADAT SERAWAI DI KABUPATEN BENGKULU SELATAN - Irwan irwan (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: The philosophical meaning of “Madu Kulau” in the procession of Ceremonial Ceremony of Adat Serawai in South Bengkulu Regency can be concluded by the Chairman of the committee (tuau kerjau) facing the adat leader by bringing forth while applying for permission to the adat chief. After applying for permission to the village head, the committee chairman (tuau kerjau) faces the head of the group from the men (tuau mendah) by unifying the two livers. Then convey the intent and purpose that will be deliberate to determine where the residence and place of business for the bride after the marriage contract is implemented. Immediately mentions selected and pre-determined gifts in honey rasan (musyawarah)10 days before the wedding procession is held. Chairman of the entourage (old mendah) responded to the rasan called by the chairman of the committee by agreeing to the selected rasan. After determining the features selected by the women’s family. The chairman of the committee (seniu kerjau) returns to the village head to present his langguwai again while giving the envelope containing the money requirement for the traditional chairman inaugurated the selected rasan in honey kulau. The adat chairman announces in front of the people present about the agreement agreed upon by both parties and inaugurated it. Then the procession of honey I closed with prayer of salvation for the groom, family and audience to get the salvation from God’s grace.